2006
DOI: 10.1099/mic.0.28924-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of whiB1 in Mycobacterium tuberculosis: role of cAMP receptor protein

Abstract: The wbl (whiB-like) genes encode putative transcription factors unique to actinomycetes. This study characterized the promoter element of one of the seven wbl genes of Mycobacterium tuberculosis, whiB1 (Rv3219c). The results reveal that whiB1 is transcribed by a class I-type cAMP receptor protein (CRP)-dependent promoter, harbouring a CRP-binding site positioned at "58?5 with respect to its transcription start point. In vivo promoter activity analysis and electrophoretic mobility shift assays suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…The latter is supported by elegant studies showing that in response to carbon source starvation, E. coli FNR and ArcA (24,25) regulate the synthesis of key enzymes involved in glycolysis and tricarboxylic acid cycle. Finally, the severe growth impairment of Mtb⌬whiB3 on various carbon sources as well as the induction of WhiB2 (15), WhiB1 (26), and WhiB3 (27) upon nutrient limitation, by exogenous cAMP, and during infection, respectively, strongly suggests that some Mtb WhiB family members play an important role in sensing fluctuations in the intracellular redox state.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is supported by elegant studies showing that in response to carbon source starvation, E. coli FNR and ArcA (24,25) regulate the synthesis of key enzymes involved in glycolysis and tricarboxylic acid cycle. Finally, the severe growth impairment of Mtb⌬whiB3 on various carbon sources as well as the induction of WhiB2 (15), WhiB1 (26), and WhiB3 (27) upon nutrient limitation, by exogenous cAMP, and during infection, respectively, strongly suggests that some Mtb WhiB family members play an important role in sensing fluctuations in the intracellular redox state.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding M. tuberculosis CRP Mt , encoded by Rv3676, recognizes a similar binding motif and has been shown to regulate transcription of several promoters—for example, the serC promoter (13), the rpfA promoter (14), the whiB1 promoter (15,16) and the frdA promoter (17). Computational approaches and in vitro DNA-binding studies suggest that M. tuberculosis CRP Mt has multiple targets and is likely to share the global profile of the E. coli homologue (18–20).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of M. tuberculosis whiB1, a member of the Wbl (WhiB-like) family, is controlled positively and negatively by CRP Mt Agarwal et al, 2006). A CRP Mt binding site (CRP Mt 1) was detected in whiB1's upstream regulatory region (Smith et al, 2010) (Rickman et al, 2005).…”
Section: Crp Mt Regulonmentioning
confidence: 99%
“…A CRP Mt binding site (CRP Mt 1) was detected in whiB1's upstream regulatory region (Smith et al, 2010) (Rickman et al, 2005). Reporter assays with native and mutated promoter sequences indicated that transcription from the native, but not the mutant, promoter was affected by cAMP levels via the direct binding with CRP Mt (Agarwal et al, 2006 CtpE, methyl-accepting chemotaxis protein Table 2. Mycobaterium genes belonging to CRP regulon and their associated function regulatory effect inhibiting whiB1 expression .…”
Section: Crp Mt Regulonmentioning
confidence: 99%